(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SUMARIO: 1. Introducción - 2. Caracteres esenciales del sistema matrimonial en Irlanda del Norte - 3. La sentencia de la High Court de 9 de junio de 2017 en el caso In Re Laura Smyth - 4. Conclusiones: hacia el pleno reconocimiento de los matrimonios de creencia en las islas británicas. The recognition of the so called belief marriages in Northern Ireland: a revolutionary High Court decision (9 June 2017) ABSTRACT: In a context in which most other countries in the British Islands have allready recognised the validity of the so called belief marriages, very recently the Northern Ireland High Court has delivered its decision in the case In Re Laura Smyth, concerning the autorisation of humanist celebrants to perform a legally valid and binding humanist wedding ceremony in Northern Ireland, as it had been requested by the applicant in this case. In this extremely important decision, Mr Justice Colton declares that the initial denial by the General Register Office of the applicant’s request was in breach of section 6 of the Human Rights Act 1998 as contrary to the applicant’s rights under Article 9 and Article 14 ECHR, and consequently makes a declaration against the General Register Office in order to grant the application for the requested temporary authorisation to humanist celebrants. This paper summarizes and conducts a preliminary analysis of this decision’s content.